2016
DOI: 10.1016/j.carbpol.2016.05.066
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and selective adsorption of multi-metal ions using sulfonated cellulose as adsorbent

Abstract: Contamination of heavy metal in wastewater has caused great concerns on human life and health. Developing an efficient material to eliminate the heavy metal ions has been a popular topic in recent years. In this work, sulfonated cellulose (SC) was explored as efficient adsorbent for metal ions in solution. Thermo gravimetric analyzer (TGA), X-ray diffraction (XRD) and Fourier-transform infrared spectrometer (FTIR) first analyzed the characterizations of SC. Subsequently, effects of solution pH, adsorbent loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(34 citation statements)
references
References 20 publications
0
32
0
2
Order By: Relevance
“…It was shown that a rise in temperature expedites the binding of metal ions until an optimum of 45°C is reached. This finding is due to the fact that as the temperature rises the kinetic energy also rises which then promotes the accessibility of metal ions onto adsorbents and, in the process, reduces the time to reach adsorption equilibrium [36, 37]. Also, the reaction of amino groups with ions is exothermic and the process for the distribution of metal ions into the FGCX pores is endothermic and this positive enthalpy change is greater than the negative enthalpy change due to the formation of complexes between the amino group of FGCX and considered metal ions in solution leading to an overall positive enthalpy change [25].…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that a rise in temperature expedites the binding of metal ions until an optimum of 45°C is reached. This finding is due to the fact that as the temperature rises the kinetic energy also rises which then promotes the accessibility of metal ions onto adsorbents and, in the process, reduces the time to reach adsorption equilibrium [36, 37]. Also, the reaction of amino groups with ions is exothermic and the process for the distribution of metal ions into the FGCX pores is endothermic and this positive enthalpy change is greater than the negative enthalpy change due to the formation of complexes between the amino group of FGCX and considered metal ions in solution leading to an overall positive enthalpy change [25].…”
Section: Resultsmentioning
confidence: 99%
“…In sulfonated microcrystalline cellulose, the introduction of sulfonate groups led to an increase in negative zeta potential from -14.3 mV in neutral solution to -37.9 mV. Uptake of metal ions Fe 3+ , Pb 2+ , and Cu 2+ reduced the negative potential to −6.24, −9.7, and 14.4 mV respectively [115].…”
Section: Metal-ion Based Crosslinking On Fiber Surfaces and Interfacesmentioning
confidence: 99%
“…These materials are, however, expensive due to their way of production, and they are all based on non nanocellulosic materials (Kutsuki 2005;Yu 2013). Sulfonated cellulose materials have been studied as adsorbents for water treatment, (Dong et al 2016) and SelesorbÓ (Kaneka Corporation, Osaka, Japan) is a clinically used immunosorbent based on cellulose modified with dextrane sulfate. Further, nanocellulose has been recently used for wastewater purification (Putro et al 2017).…”
Section: Resultsmentioning
confidence: 99%